APPLICATION OF AIRWAY MANAGEMENT IN PATIENTS POST CRANIOTOMY EPIDURAL HEMATOM - Adika Citra Kinanti; Adiratna Sekar Siwi (Sekolah Tinggi Pariwisata Mataram, 2022)
Epidural Hematoma (EDH) is an extra-axial bleeding condition with clinical symptoms that commonly occur after head trauma. The typical symptom in cases of EPD is progressive loss of consciousness. The treatment of choice for EDH cases is to perform a decompressive laminectomy and evaluation of the hematoma using a craniotomy. Craniotomy action makes neurological changes characterized by seizures and changes in breathing patterns. The author's aim is to provide nursing care for post-craniotomy epidural hematoma patients who experience ineffective breathing patterns. The author uses a case study method through a nursing care approach. Action refers to providing airway management. Implementation was carried out for 3 days of treatment. Problems with ineffective breathing patterns related to neurological disorders, head injuries are partially resolved, so longer treatment is needed and collaboration with family and other medical teams is needed